Heat Adaptation Induced Cross Protection Against Ethanol Stress in Tetragenococcus halophilus: Physiological Characteristics and Proteomic Analysis - Yang, Huan; Yao, Shangjie; Zhang, Min; Wu, Chongde (Frontiers in Microbiology, 2021)
Ethanol is a toxic factor that damages membranes, disturbs metabolism, and may kill the cell. Tetragenococcus halophilus, considered as the cell factory during the manufacture of traditional fermented foods, encounters ethanol stress, which may affect the viability and fermentative performance of cells. In order to improve the ethanol tolerance of T. halophilus, a strategy based on cross protection was proposed in the current study. The results indicated that cross protection induced by heat preadaptation (45°C for 1.5 h) could significantly improve the stress tolerance (7.24-fold increase in survival) of T. halophilus upon exposure to ethanol (10% for 2.5 h). Based on this result, a combined analysis of physiological approaches and TMT-labeled proteomic technology was employed to investigate the protective mechanism of cross protection in T. halophilus. Physiological analysis showed that the heat preadapted cells exhibited a better surface phenotype, higher membrane integrity, and higher amounts of unsaturated fatty acids compared to unadapted cells. Proteomic analysis showed that a total of 163 proteins were differentially expressed in response to heat preadaptation. KEGG enrichment analysis showed that energy metabolism, membrane transport, peptidoglycan biosynthesis, and genetic information processing were the most abundant metabolic pathways after heat preadaptation. Three proteins (GpmA, AtpB, and TpiA) involved in energy metabolism and four proteins (ManM, OpuC, YidC, and HPr) related to membrane transport were up-regulated after heat preadaptation. In all, the results of this study may help understand the protective mechanisms of preadaptation and contribute to the improvement of the stress resistance of T. halophilus during industrial processes.